2019
DOI: 10.1001/jamanetworkopen.2019.13612
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatment With 5α-Reductase Inhibitors and Prostate Cancer Mortality Among Older Adults

Abstract: This cohort study examines the association between use of 5α-reductase inhibitors and prostate cancer mortality among US Medicare beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…12,30 The present cohort study would benefit from an unprecedented covariate balance because, to our knowledge, no previous study has used matching methods when exploring the association between 5-ARIs and urological cancers. [3][4][5][6][7][8]18 The findings in this study align with those of a previous study by Mäkelä et al, 18 who observed lower BC death (HR, 0.84; 95% CI, 0.73-0.97) in patients who filled a 5-ARI prescription than in those who did not use the drug. Mäkelä et al 18 also observed fewer cystectomies (6.8% vs 9.4%) and chemotherapies (20.1% vs 22.8%) in patients with a 5-ARI prescription compared with those without.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…12,30 The present cohort study would benefit from an unprecedented covariate balance because, to our knowledge, no previous study has used matching methods when exploring the association between 5-ARIs and urological cancers. [3][4][5][6][7][8]18 The findings in this study align with those of a previous study by Mäkelä et al, 18 who observed lower BC death (HR, 0.84; 95% CI, 0.73-0.97) in patients who filled a 5-ARI prescription than in those who did not use the drug. Mäkelä et al 18 also observed fewer cystectomies (6.8% vs 9.4%) and chemotherapies (20.1% vs 22.8%) in patients with a 5-ARI prescription compared with those without.…”
Section: Discussionsupporting
confidence: 91%
“…The large Prostate Cancer Prevention Trial (PCPT) initially showed the prostate cancer–protective properties of 5-ARI, although high-grade prostate cancer was paradoxically higher in those receiving 5-ARI. This finding was validated by those of other cohort studies . In contrast, the association between 5-ARI and urothelial BC, another cancer experienced predominantly by males, remains unknown.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, in the radiomic feature selection phase, cases without kallikreins were included to improve sample size. Subsequently, to avoid bias brought by the effect that 5-alpha-reductase inhibitor (5-ARI) medication has on PSA and PSA-based kallikreins, [22][23][24] we identified cases that were not taking 5-ARI medication within 6 months of bpMRI examination and only included those in the modeling, validation and external testing phases. Inclusion of cases in each of the study phases is shown in Fig.…”
Section: Data Analyses and Modelingmentioning
confidence: 99%
“…Among 1200 unique records screened, 11 studies met our inclusion criteria (Table). One study was an RCT, and 10 were registry-based cohort studies.…”
Section: Resultsmentioning
confidence: 99%